Cardiac injury after acute carbon monoxide poisoning and its clinical treatment scheme - Geng, Shoumeng; Hao, Xiaoyan; Xu, Haicang; Yao, Jian; He, Dongyong; Xin, Hui; Gong, Xingji; Zhang, Rui (Experimental and therapeutic medicine, 2020)
This study was designed to investigate cardiac injury after acute carbon monoxide poisoning and its clinical treatment scheme. Seventy patients with moderate and severe acute carbon monoxide poisoning (ACOP) admitted from January 2017 to December 2018 into The Affiliated Hospital of Qingdao University were regarded as a research group (RG), and another 30 healthy adults undergoing physical examination in the hospital during the same period were selected as a control group (CG). Thirty-five patients in the RG who received hyperbaric oxygen therapy were considered as group A, and 35 patients who received extracorporeal membrane oxygenation therapy were considered as group B. The effective rates and complications of the two groups after treatment were compared. The concentrations of creatine kinase isoenzyme (CK-MB) and lactate dehydrogenase (LDH) of myocardial enzymes at different time points before and after treatment were detected. Expression of miR-30a in the blood of experimental subjects was detected by time-fluorescence quantitative PCR, and the relationship between miR-30a expression and ACOP patients was analyzed. Patients in groups A and B achieved obvious efficacy, but the effective rate and incidence rate of complications in the extracorporeal membrane oxygenation (ECMO) group were better than those in the hyperbaric oxygen group. The concentrations of CK-MB and LDH in group A and group B were significantly higher than those in control group (P<0.01). The expression level of miR-30a in the RG was significantly higher than that in the control group (P<0.05). Both hyperbaric oxygen therapy and ECMO therapy have obvious efficacy on ACOP patients, but the latter is better than the former. The expression level of miR-30a in blood of ACOP patients increased significantly, which is positively correlated with myocardial injury, and it decreased after treatment. It is believed that miR-30a can provide a reference index for early diagnosis and prediction of disease progression and prognosis in cardiac injury of ACOP.